Epifaunal Gastropods Diversity in Small Island Waters of Batam City Border Region - Raja Indra Saputra; Ramses Ramses; Fauziah Syamsi; Dahrul Aman Harahap; Romie Jhonnerie (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
This research examines gastropod epifauna diversity across ten small islands in Batam City, which directly borders international shipping lanes. Data collection was occurred in rocky intertidal zones using sweep sampling. The inventory revealed 12 gastropod species from 8 families, with a total abundance of 7,913 individuals. Nerita undata, Trochus marmoratus, and Euchelus atratus species dominated, contributing 56.80% to the total individuals found. The Shannon-Wiener index (H') values ranged from 1.458 to 2.103, indicating moderate diversity with moderate ecological pressure. The relatively high evenness index (E) (0.762–0.921) shows an even distribution of individuals between islands, while the low dominance index (C) (0.147–0.371) confirms the absence of genuinely dominant species. Pearson correlation analysis reveals that water clarity significantly correlated with diversity (P <0.05), whereas salinity and current velocity influence species distribution. Anthropogenic activities manifest through TDS and pH value variations affecting gastropod community stability, particularly in shipping and shipbuilding industries. These results emphasize the importance of environmental quality monitoring and implementation of sustainable conservation programs in Batam City's border areas. Future research should highlight population genetic dynamics and adaptive responses of gastropods to habitat changes. A holistic approach involving stakeholders becomes necessary to maintain biodiversity conservation and ecosystem sustainability.